The Needs Analysis of English Learning on Nursing Students - WIBOWO, AGUS (Lingustic, Literature and English Education, 2021)
The process of teaching and learning English in universities often encounters obstacles in their efforts to achieve learning objectives. The obstacle that often arises is the inadequate learning plan so that it affects the material and implementation of the learning process which is sometimes not in accordance with the field of science that is being studied by students. Seeing this, it is very important to plan learning by conducting a needs analysis based on students' needs for learning English. This study aims to analyse the need for learning English based on four basic skills and also to identify and describe the needs of nursing students’ mastery of the English language. This research was conducted using a qualitative descriptive approach. The object of this research is first year nursing students at STIKES NOTOKUSUMO. The data obtained illustrates that the purpose and motivation of students to learn English is to support academic development and be able to speak English. While their main obstacle is in terms of vocabulary mastery and understanding of grammar. The results of the analysis of English learning needs concluded that the importance of speaking and emphasis on grammar and vocabulary is needed to improve English language skills, especially for nursing students.